PERANCANGAN PROTOTIPE SIZING MACHINE GUNA MEMPERMUDAH PEMILAHAN BIJI KOPI - Saepuddin, Ahmad; Adiwibowo, Priyo Heru; Drastiawati, Novi Sukma (Program Studi Pendidikan Teknik Mesin, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Palangka Raya, 2024)
The aim of the research is to design a tool that can assist coffee farmers in determining the quality of the coffee beans produced according to the desired grade value of the coffee beans. The tool is designed to be able to fulfill the functional value produced by the tool. So that farmers can work fast, save time in the process of grading and sorting coffee beans, able to minimize operational costs, and save energy. With an electric motor power of 1 hp, the sizing machine is capable of sorting coffee with a capacity of ±250 kg/hour, therefore a day's the process of sorting 500 kg of coffee can be achieved in less than 2 hours. This really helps coffee farmers in determining the quality of coffee beans without taking a long time.